Changes in the architecture of fluvial deposits in the Paganzo Basin (Upper Paleozoic of San Juan province): an example of sea level and climatic controls on the development of coastal fluvial environments - A. TEDESCO; P. CICCIOLI; J. SURIANO; C.O. LIMARINO (Geologica Acta, 2011)
Paganzo Group exposures (Tupe Formation) in the Huaco area provide an excellent opportunity for assessing the role of sea level and climatic changes on the morphology and nature of coastal fluvial systems deposited in areas of limited tectonic activity. The paleogeographic position of Huaco, close to a coastal region within the Paganzo Basin, allows identification of the effects of sea level change on fluvial architecture. Despite the fact that the Huaco area was dominated by coastal fluvial systems, three marine incursions flooded this part of the basin during the Namurian, Early Pennsylvanian and Late Pennsylvanian respectively. During deposition of the Paganzo Group, climatic conditions evolved from glacial (Namurian) to hot and dry (Late Cisuralian). Five types of fluvial deposits were recognized on the basis of architectural element analysis, lithofacies distribution and type of fluvial bounding surfaces present. Fluvial system 1 (FS1) constitutes the lower part of the Tupe Formation and consists of stacked multi-storey channel-fill complexes formed on large braided alluvial plains dominated by channel-avulsion processes. FS2 consists of multi-storey channels alternating with floodplain deposits including coal beds and organic-rich mudstones. This fluvial system is interpreted as the deposit of an anastomosed network of sandy channels. FS3 occurs between the Early Pennsylvanian and Late Pennsylvanian marine transgressions and consists of sandstones and some conglomerates that form stacked channel complexes. Sporadically, very fine-grained sandstone and mudstone floodplain deposits appear as thin intercalations. FS3 likely formed on braided alluvial plains with channels dominated by transversal bars. FS4 corresponds to an anastomosed fluvial system that was dominated by two types of braided channel belts that were separated by narrow floodplains. Finally, FS5 is composed of fining-upward cycles ranging from gravely sandstones at the bottom of channels to muddy floodplain deposits at the top. The whole FS5 succession was deposited by high-sinuosity meandering rivers. Detailed stratigraphic analyses clearly suggest that both, sea level and climate changes were first-order controls on fluvial system configurations. In this way, braided systems belonging to FS1 correspond to a low-accommodation system tract. Whereas, coal beds of FS2, which resulted from high water-tables, correspond to a high accommodation system tract that was likely associated with advanced stages of the Late Pennsylvanian transgression. A significant change in the nature of fluvial deposits took place prior to the Late Pennsylvanian sea level rise when braided fluvial systems (FS3) with very scarce floodplain deposits prevailed. Towards the top of the Late Pennsylvanian transgressive deposits, a high relief fluvial incision surface was carved into the underlying marine deposits. This surface was later mantled by anastomosed rivers (FS4) corresponding to low-accommodation deposits formed in a lowstand or during the early stages of the ensuing sea level rise. In later phases of this transgression, high accommodation conditions prevailed and fluvial sedimentation was dominated by high-sinuosity rivers (FS5). These fluvial deposits are considered as an inland equivalent to the shallow-marine deposits exposed in the neighboring Agua Negra Formation located to the west.